Repetitive Transcranial Magnetic Stimulation Improved Source Memory and Modulated Recollection-Based Retrieval in Healthy Older Adults - Cui, Xiaoyu; Ren, Weicong; Zheng, Zhiwei; Li, Juan (Frontiers in Psychology, 2020)
Source memory is one of the cognitive abilities that are most vulnerable to aging. Luckily, the brain plasticity could be modulated to counteract the decline. The repetitive transcranial magnetic stimulation (rTMS), a relatively noninvasive neuro-modulatory technique, could directly modulate neural excitability in the targeted cortical areas. Here we are interested in whether the application of rTMS could enhance the source memory performance in healthy older adults. In addition, event-related potentials (ERPs) were employed to explore the specific retrieval process that rTMS could affect. Subjects were randomly assigned to either the rTMS group or the sham group. The rTMS group received 10 sessions (20 minutes per session) of 10 Hz rTMS applying on the right dorsolateral prefrontal cortex (i.e., F4 site), and the sham group received 10 sessions of sham stimulation. Both groups performed source memory tests before and after the intervention while the electroencephalogram (EEG) was recorded during the retrieval process. Behavioral results showed that the source memory performance was significantly improved after rTMS compared with the sham stimulation; ERPs results showed that during the retrieval phase, the left parietal old/new effect, which reflected the process of recollection common to both young and old adults, increased in the rTMS group compared to sham stimulation, while the late reversed old-new effect specific to the source retrieval of older adults remained unchanged. The present results suggested that rTMS could be an effective intervention to improve source memory performance in healthy older adults and it selectively facilitated the youth-like recollection process during retrieval. This study was registered in the Chinese clinical trial registry (CHICTR) with the identifier chictr-ire-15006371.